라니비주맙 치료에 반응이 제한적인 습성황반변성에서 3회 애플리버셉트 주입술의 효과 - 김경민(Kyung Min Kim), 김재휘(Jae Hui Kim), 장영석(Young Suk Chang), 김종우(Jong Woo Kim), 김철구(Chul Gu Kim), 이동원(Dong Won Lee) (Daihan angwa haghoi jabji, 2017)
목적: 최초 3회 라니비주맙 주입술에 반응이 제한적인 습성황반변성을 대상으로 한 2개월 간격 3회 애플리버셉트 주입술의 임상 결과를 알아보고자 한다. 대상과 방법: 습성황반변성으로 진단된 후 1개월 간격으로 3회 라니비주맙 주입술을 시행 받았으나 반응이 없어 2개월 간격으로 3회 애플리버셉트 주입술을 추가로 시행 받은 21명의 환자를 대상으로 후향적 의무기록 분석을 시행하였다. 진단 시, 라니비주맙 치료 후 1개월 및 애플리버셉트 치료 후 1개월에 측정된 시력과 중심망막두께를 서로 비교하였다. 결과: 최초 진단 시, 라니비주맙 치료 후, 및 애플리버셉트 치료 후 측정된 평균 logarithm of minimal angle of resolution (logMAR) 시력은 각각 0.62 ± 0.29, 0.73 ± 0.31 및 0.65 ± 0.28이었으며, 중심망막두께는 각각 427.0 ± 98.7 μm, 409.5 ± 78.7 μm 및 315.9 ± 98.2 μm였다. 라니비주맙 주입술 후와 비교하였을 때 애플리버셉트 주입술 후 유의한 중심망막두께의 감소가 나타났으나(p<0.001) 시력은 차이가 없었다(p=0.092). 애플리버셉트 주입술 후 시력이 호전된 경우는 8안(38.1%)이었으며, 11안(52.4%)의 경우 시력의 변화가 없었다. 애플리버셉트 주입술 후 18안(85.7%)에서 중심망막두께가 감소하였다. 결론: 최초 3회 라니비주맙 주입술에 반응이 제한적인 환자를 대상으로 한 2개월 간격 3회 애플리버셉트 주입술은 시력을 유지시키거나 호전시키고 망막 두께를 감소시키는 데 유용한 치료 방법으로 생각된다. Purpose: To evaluate the efficacy of 3 bimonthly aflibercept injections for neovascular age-related macular degeneration (AMD) that showed limited response to 3 initial ranibizumab injections. Methods: Three bimonthly aflibercept injections were performed for 21 eyes with neovascular AMD that was refractory to 3 monthly ranibizumab injections. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were measured at diagnosis, 1 month after 3 ranibizumab injections, and 1 month after 3 aflibercept injections, and these values were compared. Results: The mean logarithm of minimal angle of resolution (logMAR) BCVA at diagnosis, after ranibizumab therapy, and after aflibercept therapy was 0.62 ± 0.29, 0.73 ± 0.31, and 0.65 ± 0.28, respectively. The CRT at the aforementioned times was 427.0 ± 98.7 μm, 409.5 ± 78.7 μm, and 315.9 ± 98.2 μm, respectively. When compared with the value measured after ranibizumab therapy, CRT was significantly decreased after aflibercept therapy (p < 0.001), whereas there was no significant difference in BCVA (p = 0.092) between the two times. Improved BCVA was noted in 8 eyes (38.1%) after aflibercept therapy and BCVA was unchanged in 11 eyes (52.4%). Decreased CRT was noted in 18 eyes (85.7%) after aflibercept therapy. Conclusions: Three bimonthly aflibercept injections were found to be useful in terms of improving or maintaining visual acuity, as well as reducing retinal thickness in neovascular AMD that showed limited response to 3 initial ranibizumab injections. KCI Citation Count: 2